Готичні медальйонні раки в Сілезії - Регульська, Г. (Студії мистецтвознавчі, 2008)
The article discusses Silesian examples of Gothic reliquary medallions (German: Kapselreliquaire) extremely popular throughout Central Europe. In the 15th c. and the 1st quarter of the 16th c. in many Silesian churches, particularly in Wrocław, there were up to some dozen of those.